Navigating Digital Frontiers : Preliminary Ethical Reflections on Islamic Learning in Contemporary Nigerian Muslim Societies - Fahm, AbulGafar Olawale; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2025)
This paper examines the ethical implications of the digital transformation in Islamic learning within contemporary Nigerian Muslim societies. It explores how digital platforms have reshaped educational practices, expanded access to Islamic knowledge, and introduced new challenges regarding authenticity, authority, and equitable access. The study investigates the interplay between traditional pedagogical methods and modern digital tools using a mixed-methods approach that integrates qualitative insights and quantitative data from extensive surveys. The findings highlight opportunities and dilemmas: while digital technologies democratize learning and enhance connectivity, they also raise concerns over misinformation and the erosion of established scholarly hierarchies. The paper concludes with reflections on the need for robust ethical frameworks and policy interventions to safeguard the integrity of Islamic education in the digital age.
Keywords: Digital Islamic Learning; Digital Ethics; Nigerian Muslim Societies; Religious Education; Digital Pedagogy